Benjamin S. Gantt papers - Gantt, Benjamin S., -1852.
Official and personal journals kept by Gantt on board the USS Fairfield (Sloop of war), USS St. Louis (Sloop of war), and other ships in the U.S. Navy's Caribbean Squadron, European Station, and South Atlantic Squadron. Personal journals contain notes, verse, and descriptions of the countries visited. In his journal of the 1837-1838 cruise of the USS Independence (Ship of the line), Gantt mentions a visit on board by Nicholas I, Emperor of Russia, on July 29, 1837.
Naval officer.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Nicholas -- I, -- Emperor of Russia, -- 1796-1855.; United States. -- Navy; United States. -- Navy -- Foreign service -- Caribbean Area; United States. -- Navy -- Foreign service -- Europe; United States. -- Navy -- Foreign service -- South America; United States. -- Navy. -- Caribbean Squadron; United States. -- Navy. -- European Station; United States. -- Navy. -- South Atlantic Squadron; Fairfield (Sloop of war); Independence (Ship : 1814-1913); St. Louis (Sloop of war); Caribbean Area -- Description and travel; Europe -- Description and travel; South America -- Description and travel; Naval officers